(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Credit relations are an important component of the economic development of the state. They influence the economic processes of the country through credit policy. Credit policy, in turn, is an integral part of the bank’s overall strategy and is aimed at achieving its strategic goals. With the help of the credit policy, procedures and standards are determined, based on which bank employees provide, issue loans and manage them. Lending is one of the priority areas of the bank’s work, and currently every commercial bank provides financing to stable companies with clear business development prospects. International financial institutions play an important and significant role in the cooperation of States and multilateral diplomacy. International financial institutions were created by pooling financial resources by participating countries to expand certain tasks in the field of global economic development.